Case Report: General Anesthetic Management for Laparoscopic Cholecystectomy in Paramyotonia Congenita - McGreal, Analise; Slagle, Daniel; Dickens, Andrew (International Journal of Medical Students, 2020)
Background: Paramyotonia congenita (PC) is a rare disorder affecting skeletal muscle. Patients with this non-progressive condition experience intermittent episodes of sustained myotonia. Due to the predisposition for prolonged muscle contraction, special attention must be given to anesthetic management during operative procedures to prevent complications similar to those experienced in patients with malignant hyperthermia. To date, however, limited reports of anesthetic management in paramyotonia congenita are available. The Case: The present report describes successful general anesthetic management given to a patient with paramyotonia congenita using propofol and ketamine for induction, non-depolarizing rocuronium for muscle paralysis, and continuous nitrous oxide and IV propofol infusion for sedation. The patient remained stable throughout the case without myotonic episodes or other complications. Conclusion: Our report describes successful anesthetic management in a patient with paramyotonia congenita. This provides a potential management plan that may be applied to PC patients undergoing a variety of surgical procedures and eliminates risk associated with succinylcholine and possibly volatile anesthetics. Further research is needed to determine whether this approach is superior to previously reported techniques and should also identify which agents may be effectively utilized to reverse an intra-operative myotonic episode in PC.